The Neural Basis of Empathy and Empathic Behavior in the Context of Chronic Trauma - Levy, Jonathan; Yirmiya, Karen; Goldstein, Abraham; Feldman, Ruth (Frontiers in Psychiatry, 2019)
Background: Accumulating evidence in social neuroscience suggests that mature human empathy relies on the integration of two types of processes: a lower-order process mainly tapping into automatic and sensory mechanisms and a higher-order process involving affect and cognition and modulated by top-down control. Studies have also indicated that neural measures of empathy often correlate with behavioral measures of empathy. Yet, little is known on the effects of chronic trauma on the neural and behavioral indices of empathy and the associations among them. Methods: Mothers exposed to chronic war-related trauma and non-exposed controls (N=88, N=41 war-exposed) underwent magnetoencephalography (MEG) while watching stimuli depicting vicarious emotional distress. Maternal empathic behavior was assessed during mother-child interaction involving a joint task. Results: Empathy-evoking vignettes elicited response in alpha rhythms in a network involving both sensorimotor and viceromotor (anterior insula) regions, suggesting integration of the sensory and affective components of empathy. Whereas exposure to chronic stress did not affect the level of neural activations in this network, it reduced maternal empathic behavior. Furthermore, trauma exposure impaired the coherence of brain and behavior; only among controls, but not among trauma-exposed mothers, the neural basis of empathy was predicted by maternal empathic behavior. Conclusions: Chronic stress takes a toll on the mother's empathic ability and indirectly impacts the neural basis of empathy by disrupting the coherence of brain and behavior.